Pyloric Atresia in a Neonate With Epidermolysis Bullosa: A Case Report - Naoya Sakamoto; Kouji Masumoto; Tomohiro Aoyama; Kazuki Shirane; Yusuke Homma (Clinical Case Reports)
ABSTRACT When surgery is performed in patients with EB, risks of blisters and epidermal detachment are always present. The Heineke‐Mikulicz pyloroplasty cannot always be performed because of anatomical constraints. In such cases, it is necessary to select a more time‐consuming surgical procedure (i.e., Roux‐en‐Y gastrojejunal anastomosis) with adequate fluid management.